Women and Wage Labour in Australia and Canada, 1880-1980 - Frances, Raelene; Kealey, Linda; Sangster, Joan (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 1996)
A century of women's work history in Australia and Canada reveals both similarities and contrasts. Women workers in both countries have faced persistent occupational segregation and lower pay, justified by the "family wage" ideal of a male breadwinner and the accompanying perception of women's paid labour as secondary, less skilled and transient. While Canada's female labour force has historically demonstrated a significant proportion of immigrants from countries other than England, Australia's female labour force contained fewer immigrants but revealed a visible minority of Aboriginals who have demonstrated labour militancy in several well-known disputes in this century. Perhaps the most striking differences between the two countries, however, relate to the extent of the Australian state's involvement in wage tribunals and in the compulsory arbitration system, both of which have given women improved wages and "a floor of protection." By contrast, state intervention in Canada was minimal until well into the 20th century when minimum wage laws were passed during and after World War I. Despite these differences there are areas of similarity, particularly in this century as women workers tended to mobilize at roughly the same time, not only in unions and work places but also in neighbourhoods, ethnic communities, rural areas and to some extent in labour and left wing political groups. Modern feminist movements in both countries have waged some successful campaigns to change not only government views and agendas, but also those of trade unions. Thus, while Australian women have perhaps been more successful at "playing the state"depending on the government in power, both groups of women are increasingly faced with the challenge of government retreat from egalitarian policies under the onslaught of a right-wing, corporatist agenda.